Effects of different types of primary pterygium on changes in oculovisual function = Jenis pterigium primari dan kesannya pada perubahan fungsi okulovisual) - Hilmi, Mohd Radzi; Mohd Kamal, Khairidzan; Ariffin, Azrin Esmady; Norazmar, Nur Ain; Maruziki, Nur Nabilah; Musa, Nur Hidayah; Nasir, Mardhiah Syazwani; Che Azemin, Mohd Zulfaezal; Azami, Muhammad Hanafi; Abdul Rahim, Muhammad Afzam Shah (Universiti Kebangsaan Malaysia, 2020)
Pterygium are known to cause reduction in oculovisual function. However, the effects are varying due to its various morphological factors, thus, the impact on patient are difficult to predict which indirectly not all pterygium need to be excised. To describe the effects of different types of pterygium on changes in oculovisual function. Ninety-three (93) primary pterygium eyes from 93 patients were recruited in this study. Diagnosis and classification of primary pterygium were done by a consultant ophthalmologist (KMK). Standard optometric examinations were performed in all participants. Best-corrected visual acuity (BCVA) and contrast sensitivity (CS) was subjectively measured using computerised M&S Technologies Smart System II, performed by a single operator on the same visit. Pterygium excision was done based on a standardised method performed by a single surgeon (KMK). At third month post-surgical, repeated measurements of BCVA and CS were performed. Difference between pre and post-surgical was taken as magnitude changes for each pterygium type. Paired T-test and ANOVA were employed to evaluate the difference between pre- and post-surgical and pterygium types for both BCVA and CS parameters. Overall mean (n = 93) of BCVA and CS were found significantly associated with advance pterygium (P < 0.001). Paired T-test and ANOVA results showed a significant difference in BCVA and CS values between pterygium groups in pre- and post-surgical sessions and between pterygium types (both P < 0.001). Reduction of oculovisual function in pterygium patient is expected in advance pterygium. Management of pterygium should be coherent with pterygium types.